Coping Strategies Practiced by Breast Cancer Survivors in Duhok City, Iraq - Ali, Eman Ahmed; Al-Qazaz, Harith Khalid (Asian Pacific Journal of Cancer Care, 2025)
Background: In 2022, 8,626 new breast cancer (BC) cases were reported in Iraq, accounting for 40% of all newly diagnosed cancers. While some women learn to adapt well, others continue to struggle with the impact of the disease. Thus, we aimed to investigate the coping strategies among breast cancer survivors (BCSs) and examine their association with sociodemographic and clinical characteristics. Material and Methods: A cross- sectional study was conducted among 319 BCSs attending Azadi Hematology-Oncology Center in Duhok City, Iraq, from December 2024 to March 2025. Data on sociodemographic and clinical characteristics were collected using a structured questionnaire, and coping strategies were assessed using the Coping Orientation to Problems Experienced Inventory (Brief-COPE) questionnaire. Because the data were not normally distributed, non-parametric tests (Kruskal–Wallis and Mann–Whitney U) were used. Results: The mean age of participants was 48 years. 92.8% of the BC cases were HR-positive, and 34.5% were HER2-positive. The mean Brief-COPE score was 32.19 ± 4.23. Emotion-focused coping had the highest mean score and was significantly associated only with current BC therapy (p<0.01). Problem-focused coping came next, and was significantly associated with time since diagnosis, family monthly income, comorbidities and family history of BC (all p<0.01), as well as with menopausal status (p=0.01), age and BC stage at diagnosis (p=0.04). Lastly, avoidant coping was significantly associated with age, menopausal status, and current BC therapy (all p<0.01), as well as time since diagnosis (p=0.01) and employment status (p=0.02). Conclusion: Emotion-focused coping was the predominant coping style employed by breast cancer survivors in Duhok City, Iraq. Statistically significant associations were identified between specific coping styles and various sociodemographic and clinical characteristics, where individual differences, cultural context, and available social support systems shape survivors’ adaptation. These findings highlight the need for holistic BCSs care that addresses both medical and psychosocial needs.